Overview of Geothermal Potential in Momiwaren, South Manokwari Regency using Earth Gravity Field Analysis - Lewerissa, Richard (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2020)
West Papua province has a geothermal resource that can be established as renewable electricity energy or tourism. One of the locations for geothermal prospects is in the Momiwaren district of South Manokwari regency. A preliminary study in form of a qualitative interpretation has been conducted through the analysis of high-resolution of earth gravity fields from the Global Gravity Map developed by Curtin University, Australia. This research was performed to increase the boundary of the geological structure which indicates the existence of a source of manifestation of hotsprings and the fault structures that control it. The study begins with the reduction of the gravity field data to obtain a complete Bouguer anomaly based on the SRTM2gravity terrain model correction. Furthermore, regional and residual gravity anomalies are separated, and vertical and horizontal gravitational gradient analysis using 2-D fast Fourier transform. Qualitative interpretation produces models and boundaries of the main structure and the corresponding Demini and Gaya Baru faults and the distribution of the geological rock formations in the study area. This interpretation provides useful information as a constraint for quantitative interpretation through subsurface inversion modeling to obtain detailed geothermal models in Momiwaren.